(3OQGSI JMdjdjI hJWHjbjIs - (3fHjd GSeGYjd(B, (3YeQs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s, 2002)
(3JLO aj gPG GdcJGH (B: (3aj eaghe GdSdWI GdJbOjQjI HhLg YGe , eGgjI GdJbOjQ GdehVhYj GdbVGFj , eGgjI GdJbOjQ GdTNUj aj GdYed GdbVGFjs
(3GdeQGLY U(B.540s
Keywords: (3GdSdWIs; (3GdbGfhfs